The Impact of Roster Characteristics on Employee Wellbeing and Productivity: A focused literature review for RTIO - Andrei, Daniela; Griffin, Mark; Jorritsma, Karina; O'Neill, Liam; Fruhen, Laura (Centre for Safety, 2015)
As part of a broader focus on productivity, Rio Tinto Iron Ore (RTIO) is exploring the impact of roster designs on employee well-being and productivity. In particular, changes to roster characteristics such as compression and length have the potential to impact on employees in multiple ways. Following internal reviews and discussions with industry, RTIO wish to undertake a deeper analysis of the current scientific literature on this topic. To this end, RTIO engaged the Centre for Safety (C4S) to conduct a literature review of relevant research to enable a better understanding of the impact of different roster configurations on well-being and employee productivity.